Current insights into the functional roles of ferroptosis in musculoskeletal diseases and therapeutic implications - Zhang, Fan; Yan, Yuanliang; Cai, Yuan; Liang, Qiuju; Liu, Yuanhong; Peng, Bi; Xu, Zhijie; Liu, Wei (Frontiers in Cell and Developmental Biology, 2023)
Ferroptosis is a novel type of cell death associated with iron accumulation and excessive lipid peroxidation. Elucidating the underlying molecular mechanisms of ferroptosis is intensively related to the development and treatment of multiple diseases, including musculoskeletal disorders. Moreover, in vitro and in vivo studies have shown the importance of oxidative stress in musculoskeletal conditions such as osteoporosis, osteoarthritis, rheumatoid arthritis, and osteosarcoma. Ferroptosis-derived clinical management of musculoskeletal diseases offers tremendous and attractive opportunities. Notably, ferroptosis agonists have been proven to participate in the resistance to therapeutic agents in osteosarcoma cells, thereby enhancing the sensitivity of tumor cells to conventional therapeutic strategies. In this review, we have mainly focused on the implications of ferroptosis regulation in the pathophysiology and therapeutic response of musculoskeletal disorders. Understanding ferroptosis modulation for controlling musculoskeletal diseases might provide directions for ferroptosis-driven therapies that could be promising for the development of novel therapeutic strategies.